PERENCANAAN RUTE DISTRIBUSI INFUS DENGAN METODE DISTRIBUSI REQUIREMENT PLANNING DAN VEHICLE ROUTING PROBLEM UNTUK MENINGKATKAN EFISIENSI BIAYA OPERASIONAL (STUDI KASUS : PT. SATORIA ANEKA INDUSTRI SURABAYA) - Muhammad Heri Apriyono Heri; Ratna Diah Yuniawati (Ekliptika, 2024)
PT. Satoria Aneka Industri Surabaya is a type of pharmaceutical company in East Java which has spread to various cities and regencies throughout East Java and even outside Java where this company produces infusion fluid type products, namely RL 500 ml and NS 500 ml products. The results showed that the combined DRP and VRP approach could significantly improve the efficiency of infusion distribution. Such as determining a more optimal travel distance and minimizing delivery costs in 3 consumer locations by predicting the travel distance, namely 184.6 Km with a time of 5 hours 13 minutes and operational costs for the Company's method, namely Rp. 6,480,000.-with the EOQ method above, the total for 1 truck is 4,323,896 Pcs. so that there are no delays in delivery, so look for the best route to take, namely using the DRP and VRP methods as the right solution for the Company.